Modelling of transport processes and associated thermodynamic irreversibilities in ignition and combustion of a pulverized coal particle - Mondal S.S. (My University, 2025)
A comprehensive mathematical model of various physical processes and associated thermodynamic irreversibilities of combustion of a pulverized coal particle in the surrounding of a quiescent hot gas has been developed. The model is based on the solutions of spherico-symmetric conservation equations of heat, mass and momentum transport in both the gas and solid phases in consideration of homogeneous and interphase heterogeneous chemical reactions. The reactions are assumed to be irreversible ones and have been considered by suitable models of chemical kinetics. The thermodynamic irreversibilities due to transport processes and chemical reactions in gas phase have been determined from the generalized entropy conservation equation. The influences of coal particle diameter, coal composition and the free stream gas phase temperature on (i) temperature and life histories of burning coal particles, (ii) possible ignition states and (iii) temporal variations of process irreversibilities have been established. © 2007 Elsevier Masson SAS. All rights reserved.